Lactococcus lactis strain A5 producing nisin-like bacteriocin active against gram positive and negative bacteria - Azhar, Nur Shazana; Md Zin, Noor Hasniza; Tengku Abdul Hamid, Tengku Haziyamin (Penerbit Universiti Sains Malaysia, 2017)
In this study, a Lactic acid bacteria (LAB) strain was isolated on MRS medium from gastrointestinal tissues of Broadhead catfish (Clarias macrocephalus). Out of 50 isolates, 25 isolates were found to be positive on lactose utilization test and was identified to be Gram positive cocci. Using disc diffusion methods, one out of 22 isolates, i.e., a strain A5 demonstrated inhibitions against three indicator organisms; Bacillus cereus, Staphylococcus aureus and Salmonella thyphimurium. Partial 16S rDNA sequencing identified isolate A5 as a member of Lactococcus lactis, with 100% DNA homology. Cell free supernatant fluid from Lactococcus lactis A5 showed inhibitory activities against both gram positive pathogens (Bacillus cereus and Staphylococcus aureus) and gram negative pathogens (Salmonella thyphimurium). Chloroform precipitated bacteriocin retained antagonistic activities in the presence of catalase and lysozyme; and was completely inactivated by Proteinase K treatment. The bacteriocin has a molecular weight of 3.4 kDa, based on SDS-PAGE analysis and the extract was heat stable at 37°C and 65°C, for 15 minutes. The antibacterial activity was suppressed with the addition of EDTA but was significantly increased with the addition of SDS, Triton X-100, Tween 20 and Tween 80. This bacteriocin belongs to class 1 bacteriocin, which was shown to have a nisin-like properties. This strain can be used as potential probiotics in animal or aquaculture feeding; and the bacteriocin it produces will be useful in food preservative.